Implementation of Outcome-Based Education Learning Model in Developing Students' Soft Skills in Journalism Course - Nazikhah, Ridha Khusnun; Imam Machali; Lina; Jessika Ahali Jannah Author; Tsaqif Rahman Wildan Barikna (Indonesian Journal of Action Research, 2025)
Purpose – This study aims to analyze the implementation of the Outcome-Based Education (OBE) learning model in developing students' soft skills in journalism courses at the Islamic Religious Education (PAI) Study Program at IIQ An Nur Yogyakarta.  Design/methods – This study used a qualitative approach with a case study design. Data were obtained through participatory observation, in-depth interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. Findings – The results showed that the implementation of OBE was carried out through structured planning, implementation, and evaluation stages. Lecturers set learning outcomes from the beginning, divide students into groups, assign job descriptions, and direct them to produce digital journalistic works. This process encouraged the development of students' soft skills, especially in aspects of communication, teamwork, creativity, critical thinking, responsibility, and time management. Despite obstacles such as technical limitations, group coordination, and a dense academic load, lecturers and students were able to overcome these through mentoring, continuous evaluation, and good cooperation. These findings confirm that OBE is relevant for journalism learning in Islamic educational environments because it is able to integrate academic achievement, practical skills, and student character development simultaneously.